A DECADE OF BIOSYSTEM ENGINEERING: INSTITUTIONAL AND NON INSTITUTIONAL DESCRIPTION OF THE COURSE - Magalhães, L. P. (Revista Brasileira de Engenharia de Biossistemas, 2020)
After more than 10 years of the creation of the first Biosystems Engineering course in Brazil, is it possible to obtain a unique definition (or description) of Biosystems Engineering? Do the descriptions on the institutional websites of the four Universities offer a similar description about the course? What keywords do these sites present in the description of Biosystems Engineering? And which non-institutional websites that describe the profession, use which words most often? To answer these questions, the texts used by the four Universities in the description of the course were mined to obtain the most used words in the characterization of the course, its relation graph and the similarity between the descriptions. The results showed low similarity between the texts, the focus on the word ’production’ as the most cited and that non-institutional texts have the term ’agriculture’ more central than institutional ones.